2016
DOI: 10.22436/jnsa.009.05.126
|View full text |Cite
|
Sign up to set email alerts
|

Optimal bounds for a Toader-type mean in terms of one-parameter quadratic and contraharmonic means

Abstract: In this paper, we present the best possible Toader mean bounds of arithmetic and quadratic means by the one-parameter quadratic and contraharmonic means. As applications in engineering and technology, we find new bounds for the complete elliptic integral of the second kind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…A bivariate function Ω: (0, ∞) × (0, ∞) ⟶ (0, ∞) is said to be a mean if min a, b { } ≤ Ω(a, b) ≤ max a, b { } for all a, b ∈ (0, ∞). Recently, the bivariate means have been the subject of intensive research [63][64][65][66][67][68][69][70][71][72][73][74][75]; in particular, many remarkable inequalities and properties for the bivariate means and their related special functions can be found in the literature [76][77][78][79][80][81][82][83][84][85].…”
Section: Applications To Special Meansmentioning
confidence: 99%
“…A bivariate function Ω: (0, ∞) × (0, ∞) ⟶ (0, ∞) is said to be a mean if min a, b { } ≤ Ω(a, b) ≤ max a, b { } for all a, b ∈ (0, ∞). Recently, the bivariate means have been the subject of intensive research [63][64][65][66][67][68][69][70][71][72][73][74][75]; in particular, many remarkable inequalities and properties for the bivariate means and their related special functions can be found in the literature [76][77][78][79][80][81][82][83][84][85].…”
Section: Applications To Special Meansmentioning
confidence: 99%
“…Author details 1 School of Continuing Education, Huzhou Vocational & Technical College, Huzhou, China. 2 College of Mathematics and Econometrics, Hunan University, Changsha, China.…”
Section: Fundingmentioning
confidence: 99%
“…Let x, y > 0. Then the arithmetic mean A(x, y), quadratic mean Q(x, y) [1], contraharmonic mean C(x, y) [2,3], and Schwab-Borchardt mean SB(x, y) [4] are given by…”
Section: Introductionmentioning
confidence: 99%
“…In [8], the authors found the best possible parameters λ 1 , µ 1 , λ 2 , µ 2 ∈ (1/2, 1) such that the double inequalities…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by inequality (1.5) and the results of [8], it is natural to ask what are the best possible parameters α i , β i (i = 1, 2, 3) and α 4 , β 4 ∈ (1/2, 1) such that the double inequalities…”
Section: Introductionmentioning
confidence: 99%